THE CONSTRUCTION OF BURDEN OF PROOF AND THE ROLE OF PSYCHIATRIC REPORTS IN PLEAS OF SELF-DEFENSE AND DURESS - Wijaya, Kurnia; Hardyansah, Rommy; Khayru, Rafadi Khan; Waskito, Sarwo; Mujito, Mujito (Gapenas Publisher, 2025)
This literature study aims to analyze the construction of the burden of proof and the evidentiary function of psychiatric/psychological reports (visum et repertum) in proving the psychological elements of noodweer (self-defense) and overmacht (force majeure) in Indonesian criminal law. Employing a normative juridical method with a qualitative literature review approach, this research examines primary and secondary legal sources. The findings indicate that the allocation of the burden of proof is not absolute. A layered model is identified: the defendant bears an initial burden to raise a credible allegation supported by prima facie evidence indicating a reasonable possibility of the justifying or excusing circumstance. Once this low threshold is met, the burden shifts to the public prosecutor to disprove the defendant's claim beyond a reasonable doubt. The study further reveals that the visum et repertum, while formally a valid piece of documentary evidence under the Criminal Procedure Code, possesses limited substantive validity in retrospectively determining a defendant's precise mental state at the time of the offense. Its determinative power is persuasive rather than conclusive, heavily dependent on the methodological quality of the examination and the judge's critical ability to assess expert testimony. The study concludes that a balanced and nuanced understanding of this proof mechanism is essential to uphold the presumption of innocence while ensuring a fair trial when psychological defenses are invoked.